Using technology-based learning tool to train facial expression recognition and emotion understanding skills of Chinese pre-schoolers with autism spectrum disorder. (20th October 2019) - Zhang, Shudong; Xia, Xuenan; Li, Simeng; Shen, Lili; Liu, Junli; Zhao, Libo; Chen, Chunhui
Abstract : Objectives: Given the pervasiveness of emotional and behavioral deficits of individuals with Autism Spectrum Disorders (ASD), there is a pressing need for effective interventions to address their difficulties on Facial Expression Recognition and Emotion Understanding (FER/EU). Qunatiandi, a structured, app-based intervention program that is designed for Chinese children with ASD was utilized in this study. Three young children (two girls and one boy; age M = 4.94 years) completed an 8-week one-on-one intervention in a rehabilitation center setting. It was hypothesized that the three children would show greater progress in their FER/EU. Methods: In this study, a modified multiple probe across the program phases design was used; the dependent variable was the percentage of unprompted correct receptive identification responses for FER/EU tests during instruction and probes. Data were taken during baseline, the endpoint of instruction sessions, and a maintenance stage followed by intervention termination. Results: Findings of the study revealed that all participants demonstrated significant improvements in social acuity, gains were mostly achieved on emotion distinguishing and understanding (above 80% of accuracy). A similar scoring pattern was also found in the maintenance probe phase. Conclusion: The study is one of only a few early intervention projects to improve FER/EU skills for children with ASD using an app-based intervention. The results demonstrated that children with ASD can experience increases in emotion distinguishing and understanding skills. Maintenance probe results showed that the interventional effect can be maintained for a period of time after intervention.